WOMEN SCIENTISTS OF SURKHANDARYA — SCIENCE DEDICATORS (TAMADDUN NURI JURNALI, 2024)
In this article, "Decree on measures to support the activities of the Women's Committee of Uzbekistan, declaring 1999 as the "Year of Women", first of all to our honorable women Analytical information is given on the basis of specific sources about women scientists who grew up in the oasis of Surkhan.